University physics - Reese, Ronald Lane (Brooks/Cole Pub. Co., 2000)
1- A mathematical toolbox: an introduction to vector analysis. 2- Kinematics. 3- Newton's laws of motion. 4- The gravitational force and the gravitational field. 5- Hooke's force law and simple harmonic oscillation . 6- Work, energy and the CWE theorem. 7- Impulse, momentum and collisions. 8- Spin and orbital motion. 9- Solids and fluids. 10- Waves. 11- Temperature, heat transfer and the first law of thermodynamics. 12- Kinetic theory. 13- The second law of thermodynamics. 14- Electric charges, electrical forces, and the electric field. 15- Electric potential energy and the electric. 16- Circuits elements independent voltage sources and capcitors. 17- Electric current resistance and dc circuit analysis. 18- Magnetic forces and magnetic field. 19- Faraday's law of electromagnetic induction. 20- Sinusoidal ac circuit analysis. 21- Geometric optics. 22- Physical optics. 23- The special theory of relativity. 24- An aperitif: modern physics. 25- An introduction to quantum mechanics.